Factors associated with the survival outcomes of patients with untreated hepatocellular carcinoma: An analysis of nationwide data - Kwon, Min Jung; Chang, Soy; Kim, Ji Hoon; Han, Ji Won; Jang, Jeong Won; Choi, Jong Young; Yoon, Seung Kew; Sung, Pil Soo (Frontiers in Oncology, 2023)
Introduction In this study, we examined the natural course of untreated hepatocellular carcinoma (HCC) and identified predictors of survival in an area where hepatitis B is the predominant cause of HCC. Methods We identified 1,045 patients with HCC who did not receive HCC treatment and were registered in the Korean Primary Liver Cancer Registry between 2008 and 2014, and were followed-up up to December 2018. Thereafter, we analyzed the clinical characteristics of patients who survived for <12 or ≥12 months. A Cox proportional regression model was used to identify the variables associated with patient survival. Results and discussion The mean age of the untreated patients at HCC diagnosis was 59.6 years, and 52.1% of patients had hepatitis B. Most untreated patients (94.2%) died during the observation period. The median survival times for each Barcelona Clinic Liver Cancer (BCLC) stage were as follows: 31.0 months for stage 0/A (n = 123), 10.0 months for stage B (n = 96), 3.0 months for stage C (n = 599), and 1.0 month for stage D (n = 227). Multivariate Cox regression analysis demonstrated that BCLC stage D (hazard ratio, 4.282; P < 0.001), model for end-stage liver disease (MELD) score ≥10 (HR, 1.484; P < 0.001), and serum alpha-fetoprotein (AFP) level ≥1,000 ng/mL (HR, 1.506; P < 0.001) were associated with poor survival outcomes in patients with untreated HCC. In untreated patients with HCC, advanced stage BCLC, serum AFP level ≥1,000 ng/mL, and MELD score ≥10 were significantly associated with overall survival.